Per-region interobserver agreement of Alberta Stroke Program Early CT Scores (ASPECTS). (5th February 2020) - Nicholson, Patrick; Hilditch, Christopher Alan; Neuhaus, Ain; Seyedsaadat, Seyed Mohammad; Benson, John Charles; Mark, Ian; Tsang, Chun On Anderson; Schaafsma, Joanna; Kallmes, David F; Krings, Timo; Brinjikji, Waleed
Abstract : Background and purpose: The Alberta Stroke Program Early CT Score (ASPECTS) is a commonly used scoring system to select patients with stroke for endovascular treatment (EVT). However, the inter- and intra-reader variability is high. Objective: To determine whether the inter- and intra-reader variability is different for various regions of the ASPECTS scoring system by evaluating the interobserver variability of ASPECTS between different readers in a per-region analysis. Materials and methods: All patients with acute ischemic stroke who proceeded to EVT in our institutions over a 4-year period were retrospectively identified from a prospectively maintained database. Images were reviewed by two experienced neuroradiologists, who recalculated the ASPECTS independently. We examined each region of the ASPECTS system to evaluate agreement between the raters in each area. Results: 375 patients were included. The median total ASPECTS was 9 (IQR 8–9). The most common region showing ischemic change was the insula, with the M6 region being least commonly affected. Overall interobserver agreement for ASPECTS using Cohen's κ was 0.56 (95% CI 0.51 to 0.61). The region with the highest agreement was the insula (κ=0.56; 0.48 to 0.64). The region with the lowest agreement was M3 (κ=0.34; 0.12 to 0.56). Agreement was relatively good when ASPECTS were dichotomized into 0–5 versus 6–10 (κ=0.66; 0.49 to 0.84). Conclusions: Substantial interobserver variability is found when calculating ASPECTS. This variability is region dependent, and practitioners should take this into account when using ASPECTS for treatment decisions in patients with acute stroke.